Role Conflict and Well-Being Among Working Students: The Viewpoint of a Full-Timer - Aulia Fernandha; Novika Grasiaswaty (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2021)
This research examines the relationship between the conflicting role and the academic well-being of students who are both studying and working. It is widely assumed that students who are both working and studying experience low academic well-being, such as getting low grades, being not confident with academic performance, and feeling removed from college activities. On the other hand, most of them also experience a conflict between the multiple roles they engage in, and this reduces their productivity. Based on the literature, role conflict often occurs in individuals who have difficulty in determining the scale of priorities and responsibilities. Previous research has shown how role conflict was related to the well-being of part-time working students. Therefore, the purpose of this research is to determine whether role conflict of full-time working students is related to their subjective well-being. This study was quantitative with questionnaire data collection technique. The participants in this study were 100 college students in private universities in Jakarta. The data analysis technique used was the Spearman correlation test. The result showed that there was no relation between role conflict of working students and their academic subjective well-being. Theoritical and practical implications are discussed later.Penelitian ini mencoba mengungkap hubungan antara konflik peran dengan kesejahteraan subjektif akademik mahasiswa yang kuliah sekaligus bekerja. Diketahui mahasiswa yang bekerja dan berkuliah mengalami indikator kesejahteraan akademik yang rendah seperti mendapat nilai yang buruk, tidak percaya diri dengan performa di perkuliahan dan tidak terikat dengan kegiatan kuliah. Di sisi lain, mereka juga banyak mengalami konflik dengan dua peran yang dilakukan sehingga menurunkan produktifitasnya. Menurut literature, konflik peran sering terjadi pada individu yang kesulitan dalam menentukan skala prioritas dan tanggung jawab. Penelitian sebelumnya, Role Conflict memiliki hubungan dengan well-being pada mahasiswa pekerja part-time. Oleh karena itu, tujuan penelitian ini adalah untuk apakah Role Conflict pada mahasiswa pekerja berhubungan dengan College Student Subjective Well-being pada mahasiswa pekerja. Penelitian ini bersifat kuantitatif dengan metode pengambilan data Kuesioner. Partisipan dalam penelitian berjumlah 100 Mahasiswa di perguruan tinggi swasta Jakarta. Teknik analisa data yang digunakan adalah uji korelasi. Hasil penelitian menunjukan bahwa tidak terdapat hubungan antara konflik mahasiswa pekerja dengan kesejahteraan subjektif akademik mahasiswa. Implikasi teoritis dan praktis didiskusikan kemudian.